(untitled) (Revista Electrónica Calidad en la Educación Superior, 2020)
This article exposes how the accreditation of Central American higher education has been addressed in a regional level, taking as its main axis the Central American Integration System (SICA). For this, a conceptual approach is made on regional cooperation and the terms used around integration. Then, the article goes further into the study of the Central American integration process and its types of regionalism, to understand its work in higher education. Also, the main instances of accreditation created in the region are shown. Thus, is possible to see the actors that are involved in this process. To conclude, although the beginning of Central American integration had an economic focus, it changes to a multidimensional approach with the creation of SICA.